Penegakan Hukum Bagi Pelaku Kekerasan Terhadap Hewan Peliharaan Studi Kasus Putusan No. 223/PID.B/2019/PN GIN - Pande Komang Tegar Iswara; I Nyoman Gede Sugiartha; Ni Made Puspasutari Ujianti (Warmadewa Press, 2025)
Animal abuse is a global phenomenon that can also be linked to individual animal welfare violations. The problems are: 1) How is the regulation of animal protection according to Law No. 41 of 2014 concerning animal husbandry and health? How is law enforcement for perpetrators of violence against pets based on a case study of Decision Number 223/PID.B/2019/PN GIN? This research uses normative research methods, The purpose of this research is to investigate and analyze animal protection laws in Indonesia and to examine law enforcement against individuals who harm pets. The laws of Law No. 41 of 2014, Law No. 5 of 1990, and Law No. 18 of 2009 regulate the protection of animals and outline responsibilities for their care. These laws prohibit violence against animals and protect certain species. In certain cases, a person has been charged with mistreating a sick dog, resulting in severe injury and death. The act was deemed a violation of the animal protection law.